2020
DOI: 10.1530/rep-18-0570
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for lysophosphatidic acid in vascular remodeling at the maternal–fetal interface

Abstract: Lysophosphatidic acid (LPA) belongs to the group of phosphorylated lipids reported as crucial mediators in the physiology of reproduction. LPA binds to G-protein-coupled receptors and regulates a wide range of female reproductive functions. This bioactive lipid has also been implicated in vascular functions during physiological and pathological conditions. In this regard, the establishment of a successful pregnancy requires proper coordination of vascular processes and remodeling of maternal blood vessels duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
1
1
0
Order By: Relevance
“…167 In contrast, an impaired LPA signaling may result in dysfunction of endothelial cells, trophoblast and vascular remodeling that may contribute to the occurrence of placental abruption, fetal demise, and pregnancy loss. 90,168,169 As previously mentioned, our early study demonstrated that the supplementation with LPA and low-dose embryos with Enpp2 −/− genotypes were absorbed in the mouse model, which was higher than that of WT or Enpp2 −/− genotype, which indicates that LPA should be also involved in the regulation of embryonic trophoblast function. 90 Therefore, the direct protective effects of LPA on trophoblast cells and placenta against pregnancy loss should not be ignored.…”
Section: Metabolism Intervention Of Dmφsupporting
confidence: 50%
See 1 more Smart Citation
“…167 In contrast, an impaired LPA signaling may result in dysfunction of endothelial cells, trophoblast and vascular remodeling that may contribute to the occurrence of placental abruption, fetal demise, and pregnancy loss. 90,168,169 As previously mentioned, our early study demonstrated that the supplementation with LPA and low-dose embryos with Enpp2 −/− genotypes were absorbed in the mouse model, which was higher than that of WT or Enpp2 −/− genotype, which indicates that LPA should be also involved in the regulation of embryonic trophoblast function. 90 Therefore, the direct protective effects of LPA on trophoblast cells and placenta against pregnancy loss should not be ignored.…”
Section: Metabolism Intervention Of Dmφsupporting
confidence: 50%
“…During the first trimester, LPA could upregulate the levels of IL‐8, monocyte chemoattractant protein‐1 (MCP‐1), and growth‐regulated oncogene‐alpha via LPA1 receptors and nuclear factor‐κB–dependent signal pathways in trophoblasts, thus regulating angiogenesis and immune homeostasis 167 . In contrast, an impaired LPA signaling may result in dysfunction of endothelial cells, trophoblast and vascular remodeling that may contribute to the occurrence of placental abruption, fetal demise, and pregnancy loss 90,168,169 . As previously mentioned, our early study demonstrated that the supplementation with LPA and low‐dose rapamycin (an autophagy inducer) in the abortion mouse model significantly promoted macrophage autophagy and infiltration, upregulated the expression of adhesion molecules, further rescued the rate of embryo loss, and increased embryo numbers and weight, and/or placenta weight 90 .…”
Section: Therapeutic Intervention Of Metabolic Targets In Pregnancy Lossmentioning
confidence: 55%